Analisis peran modal intelektual dan BOPO sebagai determinan kinerja perbankan - Serly Serly; Josephine Ardini Yaputri (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, Indonesia, 2022)
This study aims to analyze the effect of intellectual capital efficiency and BOPO to the performance of banking companies. This study raises profitability as the dependent variable and involves 41 banking companies listed on the Indonesia Stock Exchange (IDX) and has released an annual report for the 2017-2021 period. The method used is descriptive quantitative analysis with purposive sampling as the data selection method. The results of the study explain that all components of intellectual capital efficiency have no significant effect except capital employed efficiency which is an indication of bank efficiency in using physical and financial capital due to the supports bank to survive in market share. Aside of that, BOPO shows a negative effect on bank performance as the effect is inversely proportional to the concept of measuring bank performance.